Features of the use of choline alfoscerate in the complex correction of cognitive disorders in patients with alcohol dependence with encephalopathy - Markozova, Lubov M.; Vasylieva, Olga O. (Psychiatry, Neurology and Medical Psychology, 2020)
The results of studying the dynamics of clinical and psychopathological manifestations, cognitive disorders, brain electrogenesis in patients with alcohol dependence under the influence of therapy according to the treatment standards (I group) and using the drug "Cereglia" in complex correction (II group) are shown in the work. As a result of treatment revealed positive dynamics of psychopathological symptoms relief in both groups was revealed; in patients II group improving electrogenesis brain manifested a decrease of irritatie, regress polymorphic paroxysmal activity, the representation of slow-wave complexes, normalization of the ratio of alpha- and beta-rhythms, the emergence of regional differences and the reactions of absorption on the functional load clinically manifested by increase of functional activity of the brain and improving cognitive function (improving ability to work and steadfastness of focus, logic of judgments, the correctness and validity of generalizations, processes of semantic memorization, the ability to highlight the main meaning of the perceived material, the ability to analyze, understand and put into words the information received), before the performance standards, the test execution time was significantly shorter in group II patients than in group I patients (p<0.05) and was closer to the test execution time in the control group. It was found that the dynamics of cognitive functions under the influence of treatment is a marker of the degree of manifestations of encephalopathy and evaluation of the effectiveness of therapy with the use of the drug "Cereglia".